Rozwiązanie:
Równanie:
[tex]\sin 6x \cdot \cos 2x=\sin x \cdot \cos 7x[/tex]
Wykorzystamy wzór:
[tex]$\sin \alpha \cdot \cos \beta = \frac{1}{2}\Big(\sin(\alpha-\beta)+\sin (\alpha+\beta)\Big)[/tex]
Mamy:
[tex]$\frac{1}{2}\Big(\sin (6x-2x)+\sin (6x+2x)\Big)=\frac{1}{2}\Big(\sin(x-7x)+\sin(x+7x)\Big)[/tex]
[tex]\sin 4x+\sin 8x=\sin(-6x) + \sin 8x[/tex]
[tex]\sin 4x +\sin 6x = 0[/tex]
Teraz korzystamy ze wzoru:
[tex]$\sin \alpha + \sin \beta = 2 \sin \frac{\alpha+\beta }{2} \cos \frac{\alpha -\beta }{2}[/tex]
Mamy:
[tex]$2 \sin \frac{4x+6x}{2} \cos \frac{4x-6x}{2} =0[/tex]
[tex]\sin 5x \cos(-x)=0[/tex]
[tex]\sin 5x \cos x=0[/tex]
[tex]$x = \frac{k\pi }{5} \vee x=\frac{\pi}{2} +k\pi[/tex]
[tex]k \in \mathbb{Z}[/tex]